Performance of Ship Assistance Program for Fisheries - Mira, Mira (Universitas Muhammdaiyah Surakarta, 2013)
The purpose of this study identify inhibiting factors that make the program Inka Mina did not reach goal. The study uses regression analysis and correlation analysis. Correlation analysis results indicate that the strong correlation between the number of aid ships with determining factors such as the potential for fisheries, the number of fishermen, the amount of production, the number of ship, number of KUB, and the fishing port. Regression analysis results indicate that amount of aid ships in a region is in accordance with the elements set out in the technical guidance. However, a strong correlation does not necessarily determine the success of this program, because there are other factors that have not been considered (qualitative factors) , such as culture one day fishing on coastal communities, peoples habits (gear and type of size), transfer knowledge, and other factors. Assessment for this problem, government should consider the culture aspect.